2015
DOI: 10.1371/journal.pone.0125628
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Species-Diagnostic SNP Markers Mined from 454 Amplicon Sequencing Reveal Admixture Genomic Structure of Modern Citrus Varieties

Abstract: Most cultivated Citrus species originated from interspecific hybridisation between four ancestral taxa (C. reticulata, C. maxima, C. medica, and C. micrantha) with limited further interspecific recombination due to vegetative propagation. This evolution resulted in admixture genomes with frequent interspecific heterozygosity. Moreover, a major part of the phenotypic diversity of edible citrus results from the initial differentiation between these taxa. Deciphering the phylogenomic structure of citrus germplasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
88
1
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(105 citation statements)
references
References 52 publications
12
88
1
4
Order By: Relevance
“…S5). Group A includes varieties of Japanese origin that show admixture from other species (Kitajima et al, 2007;Curk et al, 2015;GarciaLor et al, 2015). Our sequencing of genes other than Ruby in satsumas (C. unshiu) suggested introgression from pummelo that is different from that documented in Ponkan and Willowleaf (Wu et al, 2014).…”
Section: Ruby In Mandarinmentioning
confidence: 99%
“…S5). Group A includes varieties of Japanese origin that show admixture from other species (Kitajima et al, 2007;Curk et al, 2015;GarciaLor et al, 2015). Our sequencing of genes other than Ruby in satsumas (C. unshiu) suggested introgression from pummelo that is different from that documented in Ponkan and Willowleaf (Wu et al, 2014).…”
Section: Ruby In Mandarinmentioning
confidence: 99%
“…As for its genetic origin, Wu et al (2014) concluded that some mandarin types like `Ponkan´ and `Willowleaf´, result from interspecific introgressions of C. maxima (pummelo) into C. reticulata (wild mandarin). Later, García-Lor et al (2015) and Curk et al (2015) confirmed that the C. maxima genome was the main genome introgressed in the C. reticulata background of the mandarin germplasm.…”
Section: Ii2 Origin and Distribution Of Cultivated Citrus Plantsmentioning
confidence: 85%
“…A few cases of unreduced pollen gametes have been reported in citrus although that the the most important naturally cultivated triploid variety (`Tahiti´ lime) was probably originated through unreduced pollen from a diploid `Mexican´ lime (Curk et al, 2015). Luro et al (2004) identified a few triploid hybrids produced by 2n pollen from three different mandarins, `King´, `Hansen´ and `Ananas´, `Star Ruby´ grapefruit and `Tarroco Rosso´ and `Sanguinelli´ sweet oranges.…”
Section: Vii1 Unreduced Gametesmentioning
confidence: 99%
See 2 more Smart Citations